Graphenes prepared by Staudenmaier, Hofmann and Hummers methods with consequent thermal exfoliation exhibit very different electrochemical properties - Poh, Hwee Ling (2013)
Large-scale fabrication of graphene is highly important for industrial and academic applications of this material. The most common large-scale preparation method is the oxidation of graphite to graphite oxide using concentrated acids in the presence of strong oxidants and consequent thermal exfoliation and reduction by thermal shock to produce reduced graphene. These oxidation methods typically use concentrated sulfuric acid (a) in combination with fuming nitric acid and KClO3 (Staudenmaier method), (b) in combination with concentrated nitric acid and KClO3 (Hofmann method) or (c) in the absence of nitric acid but in the presence of NaNO3 and KMnO4 (Hummers method). The evaluation of quality and applicability of the graphenes produced by these various methods is of high importance and is attempted side-by-side for the first time in this paper. Full-scale characterization of thermally reduced graphenes prepared by these standard methods was performed with techniques such as transmission and scanning electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy. Their applicability for electrochemical devices was further evaluated by means of cyclic voltammetry techniques. We showed that while Staudenmaier and Hofmann methods (methods that do not use potassium permanganate as oxidant) generated thermally reduced graphenes with comparable electrochemical properties, the graphene prepared by the Hummers method which uses permanganate as oxidant showed higher heterogeneous electron transfer rates and lower overpotentials as compared to graphenes prepared by the Staudenmaier or Hofmann methods. This clearly shows that the methods of preparations have dramatic influences on the materials properties and, thus, such findings are of eminent importance for practical applications as well as for academic research.